Representation of equality and gender justice in narrative discourse about the COVID-19 pandemic on social media - Nuryani, Nuryani; Sholeha, Monita; Kasman, Suf; Budiman, Arif (Islamic Communication Journal, 2024)
This study aims to describe the representation of gender equality and justice in the narrative of the Covid-19 pandemic that is developing on social media. Many narratives have developed on social media related to gender that represent various things of gender equality and justice. The data in this study is in the form of narratives that develop and spread on various social media. The social media that is the focus of this study is WhatsApp and Facebook. Data analysis used a qualitative approach, utilizing representation, gender, and linguistic theories. Based on the analysis that has been carried out, it is concluded that in the narrative about COVID-19, female greetings such as mbak (sister), nyonya (madam), and tante (aunt) are often used. However, in some narratives, the greetings mas (brother) and pakdhe are also used. In addition, it was also found that the use of interjection showed annoyance and sarcasm, such as the Corona and the virus. The diversity of greeting choices does not fully reflect the gender of the post-writer. The use of greetings in the narrative also represents the existence of images that gender influences the choice of language and the direction of the narrative on positive and negative images. Based on the findings above, this study enriches our perspective on the pattern of narrative formation in discourse analysis studies. The findings also enrich the repertoire in representation theory related to the selection of diction that represents gender equality and justice. ***** Tujuan penelitian ini adalah untuk menggambarkan representasi kesetaraan dan keadilan gender dalam narasi pandemi COVID-19 yang berkembang di media sosial. Banyak narasi-narasi yang berkembang di media sosial berkaitan dengan gender yang merepresentasikan berbagai hal kesetaraan dan keadilan gender. Data dalam penelitian ini berupa narasi-narasi yang berkembang dan tersebar di berbagai media sosial. Media sosial yang menjadi fokus dalam penelitian ini adalah WhatsApp dan Facebook. Analisis data dilakukan dengan menggunakan pendekatan kualitatif dengan memanfaatkan teori representasi, gender, dan linguistik. Berdasarkan analisis yang telah dilakukan didapatkan simpulan bahwa dalam narasi tentang COVID-19 sering menggunakan kata sapaan perempuan, seperti mbak, nyonya, dan tante. Meskipun demikian, pada beberapa narasi juga ditemukan penggunaan sapaan mas dan pakdhe. Selain itu, juga ditemukan penggunaan interjeksi yang menunjukkan kekesalan dan sindiran, seperti si Corona dan sang virus. Keberagaman pilihan sapaan tidak sepenuhnya mencerminkan jenis kelamin penulis posting-an. Penggunaan sapaan dalam narasi juga merepresentasikan adanya gambaran-gambaran bahwa gender ikut memengaruhi dalam pemilihan bahasa dan arah narasi tersebut pada gambaran yang positif dan negatif. Berdasarkan temuan di atas maka kajian ini memperkaya perspektif kita mengenai pola pembentukan narasi dalam kajian analisis wacana. Temuan tersebut juga memperkaya khazanah dalam teori representasi yang berkaitan dengan pemilihan diksi yang mewakili kesetaraan dan keadilan gender.